CO2 Laser Division of Neo-Vallecula Improves Dysphagia in the Postlaryngectomy Patient: A Case Series and Review of the Literature. (19th October 2020) - Saltagi, Mohamad Z.; Wallace, Chelsey A.; Mantravadi, Avinash V.; Sim, Michael W.
Abstract : Objectives. To review the literature on neo-vallecula diagnosis and management and to report our findings regarding 3 patients who developed neo-vallecula in the context of free-flap pharyngeal reconstruction following total laryngectomy. Methods . This case series reports three patients who developed a neo-vallecula following a laryngectomy and free-flap pharyngeal reconstruction. All three patients were treated with a CO2 laser endoscopic procedure. Results . Neo-vallecula formation is thought to be related to tension on the neopharyngeal closure or closure technique following total laryngectomy. Diagnosis may be obtained with swallow studies, videofluoroscopy, or endoscopy. Treatment has included external excision and endoscopic procedures such as stapling, harmonic scalpel excision, and laser removal. We utilized an endoscopic approach entailing the use of a CO2 laser to divide the neo-vallecula, and all our patients reported improvement in their dysphagia. Conclusions . Treatment of an anterior neo-vallecula endoscopically using a CO2 laser is an effective way to treat dysphagia in patients following total laryngectomy with free-flap pharyngeal reconstruction.